2009
DOI: 10.1161/circulationaha.108.806158
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Apoptosis Exerts Divergent Effects on Atherogenesis as a Function of Lesion Stage

Abstract: Background-Because apoptotic cell clearance appears to be defective in advanced compared with early atherosclerotic plaques, macrophage apoptosis may differentially affect plaque progression as a function of lesion stage. Methods and Results-We first evaluated the impact of targeted protection of macrophages against apoptosis at both early and advanced stages of atherosclerosis. Increased resistance of macrophages to apoptosis in early atherosclerotic lesions was associated with increased plaque burden; in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
187
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(197 citation statements)
references
References 24 publications
7
187
0
3
Order By: Relevance
“…35 Therefore, the antiapoptosis effects of macrophages in early-stage atherosclerotic lesions increase the likelihood of plaque development. 34 Our group previously confirmed that PpIX could enter athermanous plaques in the rabbit carotid artery. 5 We found that PpIX mainly targeted and accumulated in metabolically active inflammatory macrophages in the athermanous plaques of ApoE -/-mice (data not shown).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…35 Therefore, the antiapoptosis effects of macrophages in early-stage atherosclerotic lesions increase the likelihood of plaque development. 34 Our group previously confirmed that PpIX could enter athermanous plaques in the rabbit carotid artery. 5 We found that PpIX mainly targeted and accumulated in metabolically active inflammatory macrophages in the athermanous plaques of ApoE -/-mice (data not shown).…”
mentioning
confidence: 77%
“…33 Moreover, macrophages play a crucial role in the progression and instability of atherosclerotic plaques. [34][35][36] Thus, promoting the clearance of macrophages from plaques is an alternative strategy for treating AS. SDT, which combines low-intensity ultrasound with different sonosensitizers, has been demonstrated to induce apoptosis in a variety of cell types relevant to different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For infl ammation studies, cells were treated with 10 or 100 ng/ml LPS (Axxora, macrophage (AIM) decreased lesion formation in bone marrow transplantation experiments owing to an increase in macrophage apoptosis ( 25,26 ). In this setting, apoptotic cell death of foam cells at the initial stages of atherosclerosis was associated with decreased lesion progression ( 27,28 ).…”
Section: Cell Culturementioning
confidence: 99%
“…Furthermore, the 9p21 genetic locus, which impacts proliferation of vascular cells, has been associated with susceptibility to coronary artery disease (17)(18)(19). With regard to survival, apoptosis of macrophages in the plaque is detected at all stages of the disease and is not proinflammatory in early, fatty streak lesions (20,21). Mutations in Cx3cr1 and Csf1 accelerate loss of macrophages from plaques, at least in part through increased apoptosis (2,22).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of decreased efferocytosis, apoptosis leads to secondary necrosis. In this setting, accumulation of dead cell debris amplifies proinflammatory signals and triggers further monocyte recruitment (20).…”
Section: Introductionmentioning
confidence: 99%